2001
DOI: 10.1002/mrd.1122
|View full text |Cite
|
Sign up to set email alerts
|

Sulfogalactosylglycerolipid is involved in human gamete interaction

Abstract: Recent results from our laboratory have revealed the role of sulfogalactosylglycerolipid (SGG) in mouse sperm-zona pellucida (ZP) binding. In this report, we demonstrated the presence of SGG in Percoll-gradient centrifuged (PGC) human sperm by high performance thin layer chromatography with orcinol and Azure A staining, specific for glycolipids and sulfolipids, respectively. SGG in human PGC sperm was quantified by its affinity to Azure A to be 12-15 mol% of sperm lipids. Indirect immunofluorescence revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 77 publications
1
37
1
Order By: Relevance
“…3). Previous work on sperm ARSA has led to the proposal that it initiates sperm-ZP engagement by virtue of its ability to act as a receptor for sulfated sugar ligands that decorate the ZP glycoproteins (Tanphaichitr et al, 1993;White et al, 2000;Weerachatyanukul et al, 2001;Tantibhedhyangkul et al, 2002;Carmona et al, 2002a). This notion is supported by the demonstration that ARSA has the ability to bind to polysulfated glycans (Huang et al, 1984;O'Rand et al, 1988;Jones and Williams, 1990;Jones et al, 1996) and that the components of the ZP are highly sulfated in nature (Prasad et al, 2000).…”
Section: Discussionmentioning
confidence: 55%
“…3). Previous work on sperm ARSA has led to the proposal that it initiates sperm-ZP engagement by virtue of its ability to act as a receptor for sulfated sugar ligands that decorate the ZP glycoproteins (Tanphaichitr et al, 1993;White et al, 2000;Weerachatyanukul et al, 2001;Tantibhedhyangkul et al, 2002;Carmona et al, 2002a). This notion is supported by the demonstration that ARSA has the ability to bind to polysulfated glycans (Huang et al, 1984;O'Rand et al, 1988;Jones and Williams, 1990;Jones et al, 1996) and that the components of the ZP are highly sulfated in nature (Prasad et al, 2000).…”
Section: Discussionmentioning
confidence: 55%
“…used ( 13,14 ). Azure A is a cationic dye that reacts with anionic lipids, including sulfolipids ( 15,16 ).…”
Section: Methodsmentioning
confidence: 99%
“…Azure A is also useful for staining sulfolipids on thin layer chromatography (TLC) plates. The limit of detection (LOD) of the colorimetric assay for sulfolipids is around 10 µg in the original method and, despite modifi cations and improvements, is still around 0.3 µg ( 13,17 ). The LOD of Azure A staining of chromatographed lipids on high-performance (HP)TLC plates is even higher: at least 1 µg of a sulfolipid is required for detection.…”
Section: Methodsmentioning
confidence: 99%
“…However, a limited number of studies indicate a role for carbohydrate moieties of the sperm glycocalyx in early gamete interactions. Tanphaichitr et al reported that Fab antibody fragments against sulfogalactosylglycerolipid (SGG), the major sulfoglycolipid in mammalian spermatozoa, inhibited human and mouse sperm binding and that SGG-bearing liposomes bound to the human and mouse zona pellucida [70,71]. Mahony et al [72] demonstrated that mAbs against carbohydrate epitopes of CD52, a glycosylphosphatidyl inositol (GPI)-anchored sperm-surface glycoconjugate, inhibit human sperm-zona binding.…”
Section: The Sperm Glycocalyxmentioning
confidence: 99%